Study of length-weight relationship of Epinephalus diacanthus (Valenciennes, 1828) Spinycheek grouper from Mumbai, North West Coast of India - Dhanalakshmi.M, Dhanalakshmi.M; Zebajafferabidi; Karan kumar ramteke; Shivkumar; Rinkesh N Wanjari; Sudhan chandran; Abdul azzez; Harshavarthini M (Journal of Indian Fisheries Association, 2023)
The length weight relationship of Epinephelus diacanthus (Valenciennes, 1828) was assessed from Mumbai, North West coast of India. Fish samples were collected monthly between August, 2019 and February, 2020 from the trawlers of New Ferry Wharf, Mumbai. These samples were analysed using regression analysis to study the relationship between total length (L) and total weight (W), both measured with precision to the nearest 0.1 cm and 0.01 g, respectively. The length range reported was 13 to 44 cm with the weight range varying between 87 to 550 g. The parameter b was estimated to be about 3.06 with R² value of 0.883. Due to its important role as an apex predator, its conservation and management is important.